2020
DOI: 10.4153/s0008414x20000723
|View full text |Cite
|
Sign up to set email alerts
|

Some complexity results in the theory of normal numbers

Abstract: Let N () be the set of real numbers which are normal to base. A well-known result of H. Ki and T. Linton [Ki and Linton, 1994] is that N () is 0 3-complete. We show that the set N ⊥ () of reals which preserve N () under addition is also 0 3-complete. We use the characterization of N ⊥ () given by G. Rauzy in terms of an entropy-like quantity called the noise. It follows from our results that no further characterization theorems could result in a still better bound on the complexity of N ⊥ (). We compute the ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…2 One can also define D β (Π 0 α ) more generally, but this will not be relevant to this paper. 3 Technically there are two universal quantifiers, one for s and one for ǫ, but as these are consecutive, they are treated as a single quantifier Since any countable set can be written as a countable union of singleton sets and is thus in Σ 0 2 , the above theorem implies the first half of Corollary 1.1 immediately. The second half is implicit in the method of proof.…”
Section: Introductionmentioning
confidence: 96%
“…2 One can also define D β (Π 0 α ) more generally, but this will not be relevant to this paper. 3 Technically there are two universal quantifiers, one for s and one for ǫ, but as these are consecutive, they are treated as a single quantifier Since any countable set can be written as a countable union of singleton sets and is thus in Σ 0 2 , the above theorem implies the first half of Corollary 1.1 immediately. The second half is implicit in the method of proof.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, V. Becher and T. A. Slaman [5] proved that the set of numbers normal in at least one base is Σ 0 4 -complete. See also [1], [6]. Also, sets of interest in dynamics are sometimes complete at levels past the Borel hierarchy.…”
Section: Introductionmentioning
confidence: 99%
“…Since the upper noise of is defined by taking limits (and lim sups) of sequences of continuous functions of , it follows immediately that is Borel, in fact a set. In fact, in [3] it was shown that is a -complete set, which shows that it is no simpler than this.…”
Section: Introductionmentioning
confidence: 99%